Handbook of Quantitative Criminology - Piquero, Alex R.; Weisburd, David; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The Handbook of Quantitative Criminology is designed to be the authoritative volume on methodological and statistical issues in criminology and criminal justice. At a time when this field is gaining in sophistication and dealing with ever more complex empirical problems, this volume seeks to provide readers with a clear and up to date guide to quantitative criminology. Authored by leading scholars in criminology/criminal justice, the Handbook contains 35 chapters on topics in the following key areas: (1) research design, (2) experimental methods, (3) methods for overcoming data limitations, (4) innovative descriptive methods, (5) estimation techniques for theory and policy, (6) topics in multiple regression, and (7) new directions in statistical analysis. The contributions are written to be accessible to readers with a basic background in statistics and research methods, but they also provide a cutting edge view of statistical and methodological problems and questions. This book will be the go-to book for new and advanced methods in the field that will provide overviews of the key issues, with examples and figures as warranted, for students, faculty, and researchers alike.
Descriptive Approaches for Research and Policy: Innovative Descriptive Methods for Crime and Justice Problems -- Crime Mapping: Spatial and Temporal Challenges -- Look Before You Analyze: Visualizing Data in Criminal Justice -- Group-Based Trajectory Modeling: An Overview -- General Growth Mixture Analysis with Antecedents and Consequences of Change -- Spatial Regression Models in Criminology: Modeling Social Processes in the Spatial Weights Matrix -- Mixed Method Research in Criminology: Why Not Go Both Ways? -- Descriptive Approaches for Research and Policy: New Estimation Techniques for Assessing Crime and Justice Policy -- Estimating Costs of Crime -- Estimating Treatment Effects: Matching Quantification to the Question -- Meta-analysis -- Social Network Analysis -- Systematic Social Observation in Criminology -- New Directions in Assessing Design, Measurement and Data Quality -- Identifying and Addressing Response Errors in Self-Report Surveys -- Missing Data Problems in Criminological Research -- The Life Event Calendar Method in Criminological Research -- Statistical Power -- Descriptive Validity and Transparent Reporting in Randomised Controlled Trials -- Measurement Error in Criminal Justice Data -- Statistical Models of Life Events and Criminal Behavior -- Estimation of Impacts and Outcomes of Crime and Justice: Topics in Experimental Methods -- An Introduction to Experimental Criminology -- Randomized Block Designs -- Construct Validity: The Importance of Understanding the Nature of the Intervention Under Study -- Place Randomized Trials -- Longitudinal-Experimental Studies -- Multisite Trials in Criminal Justice Settings: Trials and Tribulations of Field Experiments -- Estimation of Impacts and Outcomes of Crime and Justice: Innovation in Quasi-Experimental Design -- Propensity Score Matching in Criminology and Criminal Justice -- Recent Perspectives on the Regression Discontinuity Design -- Testing Theories of Criminal Decision Making: Some Empirical Questions about Hypothetical Scenarios -- Instrumental Variables in Criminology and Criminal Justice -- Estimation of Impacts and Outcomes of Crime and Justice: Non-Experimental Approaches to Explaining Crime and Justice Outcomes -- Multilevel Analysis in the Study of Crime and Justice -- Logistic Regression Models for Categorical Outcome Variables -- Count Models in Criminology -- Statistical Analysis of Spatial Crime Data -- An Introduction to Statistical Learning from a Regression Perspective -- Estimating Effects over Time for Single and Multiple Units.
Keywords: Social sciences; Statistics; Criminology; Social sciences -- Methodology; Social Sciences; Criminology & Criminal Justice; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Methodology of the Social Sciences